2000
DOI: 10.2466/pr0.2000.87.3.707
|View full text |Cite
|
Sign up to set email alerts
|

Correlations for Serotonin Levels and Measures of Mood in a Nonclinical Sample

Abstract: The Beck Depression Inventory is frequently used to detect depression and its severity because depression is a prevalent mood disorder and is commonly treated by prescription of selective serotonin-reuptake inhibitors such as Prozac. The importance of serotonin (5-HT) in the treatment of major depression is evident but the nature of this involvement is unclear. In this study, the characteristics of platelets are employed as a peripheral model of the neuron to estimate central serotonergic activity, which is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…5-HT is also the principle regulator of mood. A study by Peirson et al [11] found lower platelet 5-HT 2 receptor function was associated with depressed mood, while Williams et al [12] demonstrated higher blood 5-HT levels were correlated with better mood. An increased mood and overall sense of well-being has been shown, in both psychiatric and physical disorders, as protective and positively correlated with resiliency behavior [13].…”
Section: Introductionmentioning
confidence: 99%
“…5-HT is also the principle regulator of mood. A study by Peirson et al [11] found lower platelet 5-HT 2 receptor function was associated with depressed mood, while Williams et al [12] demonstrated higher blood 5-HT levels were correlated with better mood. An increased mood and overall sense of well-being has been shown, in both psychiatric and physical disorders, as protective and positively correlated with resiliency behavior [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, studes of college students in Britain (Dent & Sakovshs, 1986), Australia (Lovibond & Lovibond, 1995), and North America (Dozois, Dobson, & Ahnberg, 1998) have yielded mean scores between 5 and 8 on the Beck Depression Inventory. A study at an historically White South African University yielded a higher mean score of 10.9 (Peirson & Heuchert, 2000). Against this background the authors were interested in depression scores at an historically Black South African university.…”
mentioning
confidence: 99%
“…Several studies found an association between measures related to serotonin and mood in the normal range. Lower platelet serotonin 2 receptor function was associated with lower mood in one study (34), whereas better mood was associated with higher levels of blood serotonin in another study (35). Two studies found that greater prolactin release in response to fenfluramine was associated with a more positive mood (36,37).…”
Section: Serotonin and Damentioning
confidence: 93%